Post-Stroke Mania- A Case Series - Rana, Yogi; Pathak, Abhishek; Singh, Manish; Yadav, Vishesh; Singh, Rahul (Nepal Journal of Neuroscience, 2024)
Background: Post-stroke mania is a complex neuropsychiatric phenomenon that poses challenges in both diagnosis and management. This paper presents a detailed analysis of three distinct cases, comprising two females and one male, each exhibiting post-stroke mania following cerebrovascular events. Our study aims to provide insights into the varied clinical presentations, contributing factors, and therapeutic interventions in this unique subset of stroke survivors. Case 1: A 71-year-old female experienced a left hemispheric stroke, subsequently displaying manic symptoms characterized by elevated mood, impulsivity, and increased energy. Neuroimaging revealed damage to the parieto-occipital lobe, prompting further exploration into the neural correlates of post-stroke mania. Case 2: A 51-year-old female presented with right hemiparesis. Shortly after the stroke, he manifested manic features, including decreased need for sleep and heightened irritability. Psychosocial factors and pharmacological interventions were investigated to better understand the interplay of biological and environmental influences. Case 3: A 55-year-old male suffered a left hemispheric stroke. Poststroke, she exhibited manic symptoms such as distractibility and excessive goal-directed activity. The impact of lesion location on the manifestation of post-stroke mania was explored in this case. Conclusion: Through a comprehensive analysis of these cases, we aim to contribute to the growing body of literature on post-stroke mania, shedding light on its clinical heterogeneity and paving the way for tailored treatment approaches. Recognizing the nuanced nature of post-stroke mania is crucial for healthcare providers to optimize care strategies and improve the quality of life for stroke survivors grappling with this challenging neuropsychiatric condition